Muscle spindle reinnervation using transplanted embryonic dorsal root ganglion cells after peripheral nerve transection in rats. (2nd July 2019) - Asano, Kenichi; Nakano, Tomonori; Tokutake, Katsuhiro; Ishii, Hisao; Nishizuka, Takanobu; Iwatsuki, Katsuyuki; Onishi, Tetsuro; Kurimoto, Shigeru; Yamamoto, Michiro; Tatebe, Masahiro; Hirata, Hitoshi
Abstract: Objectives: Muscle spindles are proprioceptive receptors in the skeletal muscle. Peripheral nerve injury results in a decreased number of muscle spindles and their morphologic deterioration. However, the muscle spindles recover when skeletal muscles are reinnervated with surgical procedures, such as nerve suture or nerve transfer. Morphological changes in muscle spindles by cell transplantation procedure have not been reported so far. Therefore, we hypothesized that transplantation of embryonic sensory neurons may improve sensory neurons in the skeletal muscle and reinnervate the muscle spindles. Materials and methods: We collected sensory neurons from dorsal root ganglions of 14‐day‐old rat embryos and prepared a rat model of peripheral nerve injury by performing sciatic nerve transection and allowing for a period of one week before which we performed the cell transplantations. Six months later, the morphological changes of muscle spindles in the cell transplantation group were compared with the naïve control and surgical control groups. Results: Our results demonstrated that transplantation of embryonic dorsal root ganglion cells induced regeneration of sensory nerve fibre and reinnervation of muscle spindles in the skeletal muscle. Moreover, calbindin D‐28k immunoreactivity in intrafusal muscle fibres was maintained for six months after denervation in the cell transplantation group, whereas it disappeared in the surgical control group. Conclusions: Cell transplantation therapies could serve as selective targets to modulate mechanosensory function in the skeletal muscle.